2018
DOI: 10.3390/md16080261
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Quinazolinone Alkaloids Inspired by Marine Natural Products

Abstract: Many fungal quinazolinone metabolites, which contain the methyl-indole pyrazino [1,2-b]quinazoline-3,6-dione core, have been found to possess promising antitumor activity. The purpose of this work was to synthesize the enantiomeric pairs of two members of this quinazolinone family, to explore their potential as antitumor and their ability to revert multidrug resistance. The marine natural product fiscalin B (4c), and antienantiomers (4b, 5b, and 5c) were synthesized via a one-pot approach, while the syn enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 36 publications
6
42
1
Order By: Relevance
“…The reaction carried out using microwave with high temperature resulted not only in low yields of the products in the range of 2.2 to 21.7%, but also with a high degree of epimerization (Scheme 1). Contrary to what has been found in our previous study [16] that the reaction under a microwave irradiation was regioselective and yielded only anti isomers, the synthesis of 8 , by a microwave irradiation, produced also its syn epimer, 9 [4-(benzyloxy)-1-methylbenzyl at C-1], with a 22% yield. This study suggested that microwave irradiation is beneficial for the synthesis of quinazolinone alkaloids with bulky substituents at C-1 which was previously reported as unsuccessful by Mazurkiewicz-Ganesan method [17].…”
Section: Resultscontrasting
confidence: 95%
See 3 more Smart Citations
“…The reaction carried out using microwave with high temperature resulted not only in low yields of the products in the range of 2.2 to 21.7%, but also with a high degree of epimerization (Scheme 1). Contrary to what has been found in our previous study [16] that the reaction under a microwave irradiation was regioselective and yielded only anti isomers, the synthesis of 8 , by a microwave irradiation, produced also its syn epimer, 9 [4-(benzyloxy)-1-methylbenzyl at C-1], with a 22% yield. This study suggested that microwave irradiation is beneficial for the synthesis of quinazolinone alkaloids with bulky substituents at C-1 which was previously reported as unsuccessful by Mazurkiewicz-Ganesan method [17].…”
Section: Resultscontrasting
confidence: 95%
“…Surprisingly, 4 and 5 , with three stereogenic centers, gave a higher enantiomeric ratio (er) of 99%. Similar to the previous report for fiscalin B analogs [16], the multi-step approach gave a better yield and, in most cases, higher enantiomeric ratios due to milder conditions; nonetheless, the one-pot reaction is a faster alternative to provide anti enantiomers with diversity of substituents at C-1.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, the development of novel and less toxic therapeutic agents is imperative to reduce high morbidity and mortality rates associated with HCC. Over the years, the antitumor effect of natural products has been a key therapeutic strategy for treatment of cancers [ 32 , 33 , 34 ]. Alternation of oncogenes and tumor suppressor genes could induce transformation of normal cells and tumor cells in the process of tumorigenesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%